2021
DOI: 10.3390/ijerph181910458
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Birth Satisfaction and the Risk of Postpartum Depression

Abstract: Negative experiences with childbirth might have a negative impact on a woman’s overall health, including a higher risk of postpartum depression. The aim of the study was to examine the association between birth satisfaction and the risk of postpartum depression (PPD). A 30-item version of the Birth Satisfaction Scale (BSS) and the Edinburgh Postnatal Depression Scale (EPDS) were used, as well as the Perceived Stress Scale (PSS). The study included 584 women (mean age 30.6 ± 4.9), 2 to 4 days postpartum. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
4
17
1
1
Order By: Relevance
“…Previous studies have found that the level of stress experienced during pregnancy and childbirth was significantly associated with birth dissatisfaction (15,18). We found no difference in the levels of fear of COVID-19 between parity or income groups.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Previous studies have found that the level of stress experienced during pregnancy and childbirth was significantly associated with birth dissatisfaction (15,18). We found no difference in the levels of fear of COVID-19 between parity or income groups.…”
Section: Discussioncontrasting
confidence: 53%
“…This result may be explained by delays and shortcomings in the implementation of policies and guidelines promoting physiological vaginal birth in our setting. Results from previous studies indicated that cesarean was associated with lower birth satisfaction in comparison with physiological vaginal birth (4,8,18,29,31).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Otros factores de riesgo que pueden aumentar el riesgo de padecer DPP son: estrés (estrés moderado), tipo de parto (parto por cesárea), paridad (primiparidad) y antecedentes psiquiátricos positivos 5 .…”
unclassified